Aberrant DNA methylation of PTPRG as one possible mechanism of its under‐expression in CML patients in the State of Qatar. Issue 10 (23rd July 2020) - Ismail, Mohamed A.; Samara, Muthanna; Al Sayab, Ali; Alsharshani, Mohamed; Yassin, Mohamed A.; Varadharaj, Govindarajulu; Vezzalini, Marzia; Tomasello, Luisa; Monne, Maria; Morsi, Hisham; Qoronfleh, M. Walid; Zayed, Hatem; et al.
Abstract: Background: Several studies showed that aberrant DNA methylation is involved in leukemia and cancer pathogenesis. Protein tyrosine phosphatase receptor gamma (PTPRG) expression is a natural inhibitory mechanism that is downregulated in chronic myeloid leukemia (CML) disease. The mechanism behind its downregulation has not been fully elucidated yet. Aim: This study aimed to investigate the CpG methylation status at the PTPRG locus in CML patients. Methods: Peripheral blood samples from CML patients at time of diagnosis [no tyrosine kinase inhibitors (TKIs)] ( n  = 13), failure to (TKIs) treatment ( n  = 13) and healthy controls ( n  = 6) were collected. DNA was extracted and treated with bisulfite treatment, followed by PCR, sequencing of 25 CpG sites in the promoter region and 26 CpG sites in intron‐1 region of PTPRG . The bisulfite sequencing technique was employed as a high‐resolution method. Results: CML groups (new diagnosed and failed treatment) showed significantly higher methylation levels in the promoter and intron‐1 regions of PTPRG compared to the healthy group. There were also significant differences in methylation levels of CpG sites in the promoter and intron‐1 regions amongst the groups. Conclusion: Aberrant methylation of PTPRG is potentially one of the possible mechanisms of PTPRG downregulation detected in CML. Abstract : This study delivers important message that the epigenetic silencing phenomenon via DNA hyper‐methylation resulting in decreased PTPRG protein expression which play a critical role in CML disease initiation and progression. These findings also highlight the importance of evaluation and characterization the methylation levels of PTPRG gene in CML patients worldwide. Increasing cancer societies' awareness on PTPRG methylation and its silencing effects in CML can be enriched and integrated into the international CML patients' management.